The effect of grain size on the annealing-induced phase transformation in an Al0·3CoCrFeNi high entropy alloy. (5th September 2016) - Tang, Qunhua; Huang, Yi; Cheng, Hu; Liao, Xiaozhou; Langdon, Terence G.; Dai, Pinqiang
Abstract: The annealing-induced phase transformation was investigated in coarse-grained and severely deformed nanocrystalline face-centered cubic (FCC) high entropy alloys (HEA). Increasing temperature leads to phase transformations from the FCC phase to an L12 phase and finally to a B2 phase in the coarse-grained HEA. By contrast, direct transformation from the FCC phase to the B2 phase was observed in the nanocrystalline HEA at a lower temperature. Graphical abstract: Highlights: Grain size affects annealing-induced phase transformations in Al0·3 CoCrFeNi. Coarse-grained alloy transforms from FCC to L12 and finally to B2. Nanocrystalline alloy transforms from FCC directly to B2. Rapid elemental diffusion via grain boundaries in nanocrystalline alloy suppresses L12 formation.